"Nivel de información y actitud frente al VIH/SIDA de los estudiantes de Enfermería de la Universidad Nacional de Trujillo. 2007" - Sánchez Jácobo, Luz Verónica (2008)
The present research, correlative and descriptive type, transversal style, carried out in the Nursing Faculty in the National University of Trujillo from November 2007 to March 2008 with a purpose to determine the relation between the Information and Attitude level the face of AIDS in aforenamed Nursing students. The sample was formed by 54 Nursing students random selected, the information was gotten by the following instruments: Information level in AIDS questionnaire (Reliability by Spearman – Brown proof = 0.764) and the Attitude Scale the face of AIDS (Reliability by Cronbach’s Alpha = 0,859) based on the Likert’s Method, both Instruments elaborated by Acuña and followers (2001), modified by the author. The Data were done and presented in simple and contingent descriptive statistical tables. For the analysis applied ji square statitios proof for the criterion Independence Test, in addition to analogy’s coefficient of Pearson, the findings show, does not exist significative connection between study variables.